Altering Coconut Shell Biomass to High-Ordered Graphitic Carbon with Nickel Catalyzation - Kumila, Biaunik Niski; Adityaa, Farhan; Destyofrini, Fredina; Sari, Fitri Nur Indah; Pancorowati, Dhita Azzahra; Kusuma, Hamdan Hadi (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2023)
Graphite is a carbon-based material potentially utilized in numerous applications, such as electrodes for supercapacitors, lithium-ion batteries, and absorbers for water treatment. Biomass graphite is a beneficial candidate for low-cost yet valuable graphite. In this work, coconut shells, the abundant materials with high carbon contents, were successfully transformed into valuable coconut shell graphite (CSG) using metal catalytic graphitization with nickel as a catalyst at low-temperature conditions of ~1200 °C. Nickel concentration varied between 2 mmol, 3 mmol, and 5 mmol per gram of carbon. The samples were further examined using X-ray diffraction (XRD), Raman Spectroscopy, and Transmission Electron Microscope (TEM). The high graphitization degree of ~ 72 % was confirmed by X-ray diffraction analysis. That was further supported by the high-ordered stacking carbon layer that appeared in HR-TEM images. Meanwhile, Raman spectroscopy confirms that nickel impregnation diminished the structural defect of samples and increased the sp2-carbon bond indicated by its rise of IG/ID. The IG/ID values of CGS and CGS-Ni5mmol are 0.86 and 0.92, respectively.